Menyelami Integrasi Kurikulum untuk Penerapan TPACK dalam Pembelajaran Bahasa Arab - Hasan, Laili Mas Ulliyah; Aziz, Muhammad Tareh; Rido'i, Muhammad (Global Action and Education for Society, 2024)
Curriculum integration is an important aspect in developing education that is holistic and relevant to the needs of the times. This study investigates the application of the Technology Content Pedagogical Knowledge Model (TPACK) in Arabic language learning which includes four skills: listening, speaking, reading, and writing. This research uses a qualitative approach with case studies as the main method of data collection. The research participants consisted of Arabic language teachers and students at high school. Data was collected through classroom observations, interviews with teachers, and analysis of curriculum documents. The results of the analysis show that the integration of TPACK in Arabic language learning can improve the quality of teaching and learning, as well as facilitate the development of comprehensive Arabic language skills. These findings indicate that the use of TPACK allows teachers to integrate technology with relevant curriculum and teaching strategies, thereby enriching students' learning experiences in achieving holistic Arabic language skills. The practical implication of this research is the need for ongoing training for Arabic language teachers in integrating TPACK in their learning to strengthen the quality of Arabic language education in high schools.